Pathways to Scientific Literacy: A Preliminary Study on Developing Physics E-Modules to Foster Students’ Critical Thinking Skills - Saleh, Zulfadly; Malago, Jasruddin Daud; Abdullah, Helmi (Impulse: Journal of Research and Innovation in Physics Education, 2026)
The integration of scientific literacy in physics learning is increasingly important to support students’ critical thinking skills, particularly in abstract topics such as renewable energy. However, the availability of instructional materials that align with curriculum demands and students’ characteristics remains limited. This study aims to conduct a comprehensive needs analysis as the initial stage in developing a scientific literacy-based physics e-module on renewable energy. The research employed a Research and Development (R&D) approach using the 4D model, focusing on the Define stage, which includes curriculum analysis, student analysis, concept analysis, and the formulation of instructional objectives. The study was conducted at SMAS Buqatun Mubaraqah, involving 25 tenth-grade students and one physics teacher. Data were collected through questionnaires, semi-structured interviews, and classroom observations, and analyzed using a descriptive mixed-methods approach. The results indicate a gap between curriculum expectations and existing instructional practices in supporting scientific literacy and critical thinking. Student analysis shows that visual (36%) and kinesthetic (32%) learning styles are dominant, while most students demonstrate moderate technology readiness (68%). In addition, concept analysis reveals that renewable energy topics involve abstract and dynamic processes that require visualization and interactive learning support. These findings provide a strong foundation for developing a scientific literacy-based physics e-module that aligns curriculum demands, student characteristics, and conceptual complexity to support meaningful learning and foster critical thinking skills.